Structure and Distribution of Centromeric Retrotransposons at Diploid and Allotetraploid Coffea Centromeric and Pericentromeric Regions - de Castro Nunes, Renata; Orozco-Arias, Simon; Crouzillat, Dominique; Mueller, Lukas A.; Strickler, Suzy R.; Descombes, Patrick; Fournier, Coralie; Moine, Deborah; de Kochko, Alexandre; Yuyama, Priscila M.; Vanzela, André L. L.; Guyot, Romain (Frontiers in Plant Science, 2018)
Centromeric regions of plants are generally composed of large array of satellites from a specific lineage of Gypsy LTR-retrotransposons, called Centromeric Retrotransposons. Repeated sequences interact with a specific H3 histone, playing a crucial function on kinetochore formation. To study the structure and composition of centromeric regions in the genus Coffea, we annotated and classified Centromeric Retrotransposons sequences from the allotetraploid C. arabica genome and its two diploid ancestors: Coffea canephora and C. eugenioides. Ten distinct CRC (Centromeric Retrotransposons in Coffea) families were found. The sequence mapping and FISH experiments of CRC Reverse Transcriptase domains in C. canephora, C. eugenioides and C. arabica clearly indicate a strong and specific targeting mainly onto proximal chromosome regions, which can be associated also with heterochromatin. PacBio genome sequence analyses of putative centromeric regions on C. arabica and C. canephora chromosomes showed an exceptional density of one family of CRC elements, and the complete absence of satellite arrays, contrasting with usual structure of plant centromeres. Altogether, our data suggest a specific centromere organization in Coffea, contrasting with other plant genomes.